A novel design of hard-magnetic soft switch array for planar and curved surface applications - Yang, Po; Guo, Yan; Xue, Xiaomeng; Huang, Bin (Frontiers in Materials, 2024)
This paper proposes an array structure with multidirectional remanent magnetization based on hard-magnetic soft materials, which can be used as a soft switch array on planar and curved surfaces. We firstly investigate the displacement response of a hard-magnetic soft switch which is excited by a magnetic field, and related to the magnitude and direction of the magnetic field. When the remanent magnetization direction of the soft switch is opposite to the horizontal component of the magnetic field, the displacement response is greater than that of the driving magnetic field in other directions. The maximum displacement of the soft switch can reach 4.5 mm under a 6 V driving voltage applied to the Helmholtz coil. We further design 2 × 2 and 3 × 3 switch arrays and the circuit structures of the switch arrays. The switch arrays are fabricated, and the displacement responses of the switch arrays under different driving magnetic fields on planar and curved surfaces are finally demonstrated. When the Z-axis displacement of the device reaches more than 3 mm, the LED light can be switched on. The hard-magnetic soft switch array structure designed in this paper can enable the application of soft switches in curved environments, verifying the feasibility of the application of hard-magnetic soft switch arrays. It is expected to provide a guidance for the design and manufacturing of multi-functional hard-magnetic soft switches in the future and the application of hard-magnetic soft switch arrays in planar and curved environments.